The Effect of Seating Arrangement on Student Understanding in The Subject of Force and Motion for Grade IV Students at SD N 10 Palembang - Pratama, Aldora; Kuswidyanarko, Arief; Abdullah, Septiyawan (Jurnal Inovasi Pendidikan Dasar, 2024)
This study aims to determine the effect of seating arrangement on students' understanding of the topic of force and motion among fourth-grade students at SD N 10 Palembang. This research is a quantitative experimental study using a Nonequivalent Control Group Design. Based on the results of the research that has been conducted, students' reading comprehension has improved with the use of this seating arrangement. This is evidenced by the t-test calculation resulting in t-value = 2.559 and t-table = 2.069, yielding a significance value (2-tailed) of > 0.05. Therefore, it can be concluded that the t-value > t-table, indicates that Ha is accepted and Ho is rejected. This means that the hypothesis stating that the use of seating arrangement affects the understanding of fourth-grade students at SD N 10 Palembang is accepted.